ANALYSIS OF FACTORS INFLUENCING STUDENTS' INTEREST IN LEARNING MATHEMATICS: A CASE STUDY IN PESANTREN-BASED SCHOOLS - Gunawan, Gunawan; Hidayati, Litsa Arfi; Kusuma, Jaka Wijaya; Widiyastuti, Erni; Sugihandardji, Chumaedi (International Journal of Multidisciplinary Research and Literature, 2024)
This study aims to analyze various factors that affect students' interest in learning in pesantren-based boarding schools in mathematics subjects. The subjects of the study involved were 27 grade VII students at Madrasah Tsanawiyah Minat Kesugihan, Cilacap. This study uses a qualitative descriptive method with a case study approach. Data was obtained through observation, questionnaire distribution, and interviews with students who lived in Islamic boarding schools. Data analysis is carried out inductively to understand various factors that affect students' motivation to learn. The results of the study indicate that intentual, external, and related factors related to mathematics content affect students' interest in learning mathematics subjects. The three factors have a positive role in increasing students' interest in learning mathematics. This research is expected to contribute to the development of learning strategies in schools, especially Islamic boarding schools to improve the quality of education